Implementasi Alat Pembakaran Sampah Minim Asap sebagai Alternatif Pengelolaan Sampah di Desa Pesantren Kabupaten Batang - Faiq Mananul Faqih; Muhammad Hilmy Nurul Raihan; Frina Nian Saputri; Nabila Rista Purwaningrum; Gunadi; Sukirno (MITRA: Jurnal Pemberdayaan Masyarakat, 2026)
Pesantren Village, Batang Regency, Central Java, faces serious challenges in managing organic and inorganic waste. The community still relies on open burning, which causes air pollution in the form of fine particles (PM2.5, PM10) and toxic gases such as carbon monoxide (CO), and poses a risk to respiratory health. Through the Community Service Program (KKN) at Semarang State University, an innovative, appropriate technology was developed in the form of a smoke-free waste incinerator made from a 200-liter used drum. The implementation included observation, tool design, testing, outreach and demonstration, and implementation. The result was proven to reduce smoke production by up to 80%, increase combustion efficiency, and convert organic waste into ash that can be further utilized. The outreach, which coincided with the commemoration of the 80th Indonesian Independence Day, successfully reached all elements of society and raised collective awareness of responsible waste management. This innovation proves that a simple, economical solution involving community participation can be a sustainable answer to waste problems in rural areas and has the potential to be implemented in other areas.